Expression and regulation of immune-modulatory enzyme Indoleamine 2,3-dioxygenase (IDO) by human airway epithelial cells and its effect on T cell activation - Aldajani, Wejdan A.; Salazar, Fabian; Sewell, Herb F.; Knox, Alan; Ghaemmaghami, Amir M. (Impact Journals, 2016)
Indoleamine 2,3-dioxygenase (IDO) catalyzes the degradation of tryptophan, which plays a critical role in immune suppression through regulating the production of a series of metabolites that are generally referred to as kynurenines. It has become increasingly clear that epithelial cells (ECs) play an active role in maintaining lung homeostasis by modulating the function of immune cells via producing cytokines, chemokines, and anti-microbial mediators. In this study we assessed the regulation of IDO activity and expression in human primary ECs and EC lines under steady state conditions and in response to bacterial and allergenic stimuli. We also investigated the potential immune modulatory functions of IDO expression in human airway ECs. Our data clearly show that airway ECs produce IDO, which is down-regulated in response to allergens and TLR ligands while up-regulated in response to IFN-γ. Using gene silencing, we further demonstrate that IDO plays a key role in the EC-mediated suppression of antigen-specific and polyclonal proliferation of T cells. Interestingly, our data also show that ECs lose their inhibitory effect on T cell activation in response to different TLR agonists mimicking bacterial or viral infections. In conclusion, our work provides an understanding of how IDO is regulated in ECs as well as demonstrates that “resting” ECs can suppress T cell activation in an IDO dependent manner. These data provide new insight into how ECs, through the production of IDO, can influence downstream innate and adaptive responses as part of their function in maintaining immune homeostasis in the airways.